2014
DOI: 10.1002/2013rg000437
|View full text |Cite
|
Sign up to set email alerts
|

Review of wave-driven sediment resuspension and transport in estuaries

Abstract: Waves are fundamentally important to the physical and biological functioning of estuaries.Understanding and predicting contaminant transport, development of sedimentary structures, geomorphological response to changes in external forcings such as rising sea level, and response of estuarine ecosystems to contaminant stressors require understanding of the relative roles of wave-and current-driven sediment transport. We review wave-driven sediment resuspension and transport in estuaries, including generation of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(181 citation statements)
references
References 135 publications
6
160
0
Order By: Relevance
“…DistLM showed that 39-54% of response to enrichment could be explained, most of it by macrofaunal diversity. It is difficult to speculate on the source(s) of the unexplained variation in DEA CN , but on a dynamic intertidal sandflat spatial and temporal variations in sediment biogeochemistry caused by hydrodynamic forcing (Green and Coco 2014;Huettel and others 2014), foraging and excretion by large predators (for example, Thrush and others 1994;Hines and others 1997;Jauffrais and others 2015), detrital inputs (for example, Eyre and Ferguson 2002;Eyre and others 2013) and microbial diversity (for example, Yazdani Foshtomi and others 2015) could all contribute, as could any initial small-scale variation between plots within a site. Nevertheless, the fact that a substantial proportion of the DEA response could be explained by macrofauna diversity despite the complexity of the field setting emphasises its importance in regulating the effects of enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…DistLM showed that 39-54% of response to enrichment could be explained, most of it by macrofaunal diversity. It is difficult to speculate on the source(s) of the unexplained variation in DEA CN , but on a dynamic intertidal sandflat spatial and temporal variations in sediment biogeochemistry caused by hydrodynamic forcing (Green and Coco 2014;Huettel and others 2014), foraging and excretion by large predators (for example, Thrush and others 1994;Hines and others 1997;Jauffrais and others 2015), detrital inputs (for example, Eyre and Ferguson 2002;Eyre and others 2013) and microbial diversity (for example, Yazdani Foshtomi and others 2015) could all contribute, as could any initial small-scale variation between plots within a site. Nevertheless, the fact that a substantial proportion of the DEA response could be explained by macrofauna diversity despite the complexity of the field setting emphasises its importance in regulating the effects of enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that resuspension does not occur in dry years and that it stops in April-May, it is legitimate to include water depth as a possible limiting factor of SPM resuspension. Indeed, the resuspension of lake bottom sediment occurs when the water is not too deep (otherwise, the wave-driven turbulence would not reach the lake bottom), which is never the case for ponds in this region, nor too shallow (otherwise, large waves cannot develop) [46].…”
Section: Factors Impacting Dry Season Spm Variabilitymentioning
confidence: 99%
“…Tidal asymmetries and lag effects are classically regarded as drivers of sediment import from the channels to the tidal flats, but it is unclear whether that still holds if the influence of wave forcing is considered. As an example, Green and Coco (2014) reported about studies in which waves are argued to enhance settling lag by lengthening the settling trajectories, or conversely to impair settling lag by agitating the water column and preventing settling. By means of defining a unifying framework (next Section 2.4), we will be able to assess how wave resuspension affects magnitude and direction of the tidal barotropic mechanisms.…”
Section: Wave Resuspensionmentioning
confidence: 99%
“…Wind and wave forcing influence the sediment transport patterns in the basin Lettmann et al 2009;Sassi et al 2015). In this paper, we direct our attention to the erosion of sediment by small-amplitiude waves, which has been recognized as a process of major importance for morphodynamics of tidal flats (Green and Coco 2007;Green 2011;Green and Coco (2014;Talke and Stacey 2008;Friedrichs 2012). The wave-orbital velocities influence the distribution of the bed-shear stresses and hence the sediment fluxes caused by the tidal flow.…”
Section: Introductionmentioning
confidence: 99%